2018
DOI: 10.1158/1055-9965.epi-17-0581
|View full text |Cite
|
Sign up to set email alerts
|

The Women's Health Initiative (WHI) Life and Longevity After Cancer (LILAC) Study: Description and Baseline Characteristics of Participants

Abstract: The Women's Health Initiative (WHI) Life and Longevity After Cancer (LILAC) study offers an important opportunity to advance cancer research by extending the original WHI studies to examine survivorship in women diagnosed with cancer during their participation in WHI. The goals of LILAC are to (i) obtain cancer treatment information and long-term cancer outcomes for women diagnosed with one of eight selected cancers (breast, endometrial, ovarian, lung, and colorectal cancers, and melanoma, lymphoma, and leukem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

8
1

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 11 publications
0
57
0
Order By: Relevance
“…Age at diagnosis and disease severity (stage, grade, site) were assessed at the time of CRC diagnosis. Treatment data (surgery, radiotherapy, and chemotherapy), collected through the Life and Longevity After Cancer (LILAC) study of women from the WHI diagnosed with cancer, used Medicare data in women who were diagnosed at ages ≥65 years, medical records in those who died before the LILAC study, and a combination of medical records and self‐reported data in those living participants with CRC . Treatment data were available for 67.5% of women in the study population.…”
Section: Methodsmentioning
confidence: 99%
“…Age at diagnosis and disease severity (stage, grade, site) were assessed at the time of CRC diagnosis. Treatment data (surgery, radiotherapy, and chemotherapy), collected through the Life and Longevity After Cancer (LILAC) study of women from the WHI diagnosed with cancer, used Medicare data in women who were diagnosed at ages ≥65 years, medical records in those who died before the LILAC study, and a combination of medical records and self‐reported data in those living participants with CRC . Treatment data were available for 67.5% of women in the study population.…”
Section: Methodsmentioning
confidence: 99%
“…One of the specific goals of the WHI LILAC study was to obtain cancer treatment information and late and long-term cancer outcomes for women diagnosed with 1 of 8 selected cancers (breast, endometrial, ovarian, lung, and colorectal cancers, melanoma, lymphoma, and leukemia). 16 The ultimate goal was to expand the existing WHI data to support studies of cancer outcomes, participant survivorship, and molecular epidemiology. LILAC participants were asked to complete an initial survey about their initial cancer treatments and recurrences, as well as updated demographic information, medications, symptoms, social support, financial problems, mental and physical functioning, quality of life, and unmet needs.…”
Section: Methodsmentioning
confidence: 99%
“…24 The LILAC cancer survivorship cohort was designed with three study objectives: (a) to collect treatment and outcomes information from women diagnosed with cancer during their participation in WHI; (b) to supplement the WHI biorepository with tissue samples from select solid tumors; and (c) to test the ability of electronic administrative data to produce reliable treatment and recurrence data. 21 A total of 30 306 women were diagnosed with incident cancers after enrolling in WHI. Of those, 9934 were invited to participate in LILAC after excluding women with cancers other than those selected financial burden.…”
Section: Study Participantsmentioning
confidence: 99%